Assessment of Landscape Characteristics on Spatial Distribution of Soil Moisture Index - Md Adros, Faiz Hashemi (Universiti Teknologi PETRONAS, 2017)
Water content of soil is what defines soil moisture, which is held in between the voids of the particles of soil and it plays an important role in the assessment of different components of water and energy balance. Soil moisture acts as the utmost source of water for purposes such as agriculture, and vegetation of natural plants, which influences a number of vital processes including the growth of plants, production in agriculture and a number of soil processes. The dynamics of soil moisture can be modified by a number of factors such as climate change, properties of soil, topography, and the characteristics of the landscape itself. In this study, the author is aiming to find the relationship between two main parameters, which are the distribution of soil moisture and how it is affected by the variation of landscape characteristics.